Viking Age Hair - Elisabeth Arwill-Nordbladh (Internet Archaeology, 2016)
A study of hair in the Viking Age. The article draws on medieval Icelandic and Scandinavian texts for interpretation. Further information is taken from pictoral representations of viking hair styles and decoration, hairdressing artefacts, figurines and actual remains of hair.